Pronouns in Catalan: Games of partial information and the use of linguistic resources - Mayol, Laia; Clark, Robin (Journal of pragmatics, 2010)
This paper investigates the variation between null and overt subject pronouns in Catalan, a null-subject language. We account for this variation in game-theoretical terms: that is, we analyze the distribution of both overt and null pronouns as a result of the strategic interaction between participants in a communicative exchange. First, we examine the Position of Antecedent Hypothesis (PAH), as put forward by Carminati (2002). This hypothesis proposes that null and overt pronouns have different biases: null pronouns prefer antecedents in subject positions, while overt pronouns prefer antecedents in non-subject positions. Carminati (2002) tested the PAH for Italian in a variety of intrasentential contexts. In this paper, we show experimentally that the PAH also holds for Catalan even in across-sentence contexts. In the second place, we also show how the PAH can be naturally redefined as a game of partial information, in which speaker and hearer are trying to communicate. This redefinition does not just translate the PAH into a different notation, but it extends the PAH into a model that makes more accurate predictions, since it can account also for the cases in which the biases predicted by the PAH are not obeyed.